Thalamic volume and dimensions on MRI in the pediatric population: Normative values and correlations: (A cross sectional study). Issue 109 (December 2018) - Tutunji, Rayyan; El Homsi, Maria; Saaybi, Stephanie; AL Arab, Natally; Tamim, Hani; Makki, Maha; Hourani, Mukbil; Hourani, Roula
Highlights: No current objective measures of the thalamus exist for early life. We examine the thalamic two-dimensional and volumetric development across the pediatric age group. Thalamic volumes increase until the age of four and stabilize afterwards. This study also adds normative, easy to replicate 2D-values for clinical use. Abstract: Background: Diagnoses of thalamic atrophy in children are based on experts' judgments. No normative measures exist for aiding objective diagnoses. Our aim was to determine normative two-dimensions(2D) and volume measurements of the thalamus in normally developing children. Methods: MRI images of 245 patients were retrospectively collected. Only participants with normal brain MRIs were included in this cross-sectional study. Anterior-posterior (AP), transverse (T), and craniocaudal (C) diameters were measured. Volumetric masks of the thalamus were manually drawn, whereas volumetric measurements of the brain were automated. Results: 124 patients were male (50.6%). We tabulated our measurements from birth until 18 years old. No significant differences in the thalamus measurements are found between the two hemispheres nor between sexes. The most remarkable increase in the thalamus volume and AP dimension is noted in the first four years of life, following which the values seem to stabilize. Craniocaudal diameters seem to increase in the first year of life, whereas transverse diameters increase until the age of 14 before plateauing. Conclusion: We report normative values of the thalamus in 2D and 3D from birth until 18 years of age. A rapid increase in the thalamic size is noted during the first four years of life followed by stabilization.